IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2014 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DI KOTA BATAM - Setia Laoli, Rahmat; Epriadi, Dedi (LPPM Universitas Putera Batam, 2022)
Policy implementation is a stage of public policy that has been formulated and must be realized. For this reason cooperation is needed between the Batam City Government and all stakeholders in the Batam City area to preserve the environment. The purpose of this study was to determine each process in the implementation of the Regional Regulation No. 4 of 2014 concerning Environmental Protection and Management in order to reduce environmental pollution in Batam City. This research was conducted at the Batam City Environmental Service. The author's research method is a descriptive research method with a qualitative approach and qualitative analysis methods, with the aim of focusing on the problems or phenomena that existed at the time the research was conducted, then describing the facts and explaining the state of the research object in accordance with the reality as it is, and trying to analyze to provide truth based on the data obtained. The results of the study can be concluded that the implementation of policies in general has been going well, but has not been maximized, there are still shortcomings, such as the lack of awareness on the part of companies that do not implement policies on environmental management properly. Keywords: implementation; local regulations; environment.